EXISTENTIALISM ANALYSIS OF SARTRE IN THE SHORT STORY "A CLEAN WELL-LIGHTED PLACE" BY ERNEST HEMINGWAY - Fransiska Aurelia Susana Sainin; Lailatul Musyarofah (Pro-ELLitera, 2024)
This article presents an analysis of existentialism from Sartre's viewpoint as reflected in Ernest Hemingway's short story "A Clean, Well-Lighted Place." The study investigates existential motifs such as solitude, void, the essence of existence, and internal struggles depicted through the personas of the youthful waiter, the aged waiter, and the isolated elderly individual. Utilizing a qualitative methodology, the research aims to dissect dialogues, character behaviors, and narrative construction to reveal the existentialist elements entwined within the narrative. By scrutinizing the existential themes interwoven in the storyline and juxtaposing them with Sartre's philosophical principles, the paper offers a profound exploration of the existentialist interpretation within Hemingway's literary creation.